Insights into the role of strontium in catalytic combustion of toluene over La1−xSrxCoO3 perovskite catalysts. Issue 6 (26th January 2022) - Liu, Mo; Yang, Xiaoli; Tian, Zimeng; Wang, Huimin; Yin, Liangtao; Chen, Jianjun; Guan, Qingqing; Yang, Hao; Zhang, Qiulin
Abstract : A series of LaCoO3 perovskite catalysts substituted by Sr in the A site (La1− x Sr x CoO3 ) were prepared via a facile sol–gel method. Abstract : A series of LaCoO3 perovskite catalysts substituted by Sr in the A site (La1− x Sr x CoO3 ) were prepared via a facile sol–gel method. The catalytic activity of these perovskite catalysts for the deep oxidation of toluene was evaluated. It was found that Sr substitution significantly enhanced the redox properties, the concentration of oxygen vacancies, and surface Co 3+ active species via an electron interaction between Sr and Co from the results of Raman spectroscopy, H2 -TPR (temperature programmed reduction), O2 -TPD (temperature programmed desorption) and XPS (X-ray photoelectron spectroscopy). Typically, La0.82 Sr0.18 CoO3 (L0.82 S0.18 C) exhibited a superior catalytic performance among these samples owing to its best reducibility and highest number of active species. Kinetic analysis further revealed a higher reaction rate (5.1 × 10 −7 mol g −1 ·s −1 at 210 °C) and a lower apparent activation energy (69.1 kJ mol −1 ) for toluene oxidation on the L0.82 S0.18 C sample in comparison to those on the others. In situ DRIFTS (diffuse reflectance infrared Fourier transform spectroscopy) confirmed the easy desorption of immediate products from the surface of the L0.82 S0.18 C sample, which could be responsible for its remarkable performance. These results could provide an efficient strategy for promoting the toluene oxidation through finely tuning the reducibility and surface active phase of the catalysts.